Membangun Jiwa Wirausaha Siswa Melalui Kegiatan Membatik Ecoprint (Studi Kasus Kewirausahaan Tas Batik “Godhong Kembang” di SDN Genuk 01 Ungaran Barat) - Masruroh, Masruroh (Pena Edukasia, 2023)
Entrepreneurship education is a strategy to be able to foster the entrepreneurial spirit of students from an early age. It is hoped that through entrepreneurship students can be prepared to become human beings who are independent and compete in facing challenges in the economic sector in order to live prosperously. Carrying out entrepreneurship introduction activities for grade 5 students through the activity of making ecoprit (Godhong Kembang) batik by utilizing natural materials around students. This entrepreneurial activity is integrated with learning content so that students are interested in participating in activities. With this activity, students are expected to have a skill that has a selling point. This entrepreneurship program goes through a preparatory stage, a batik socialization stage, a production stage, and the final stage is evaluation. Through batik using the Ecoprint technique students can express ideas and ideas without limits using leaf and flower shapes to produce beautiful batik works.